Analyzing Big Data Maturity for Government Crisis Management: Uncovering the Advantages of E-Government Amid Global Dynamics - Wance, Marno; Tuanaya, Wahab; Herizal, Herizal (Universitas Sultan Ageng Tirtayasa, 2025)
Big data has become a strategic tool for enhancing the effectiveness of government crisis management in the face of increasingly complex global challenges. This study aims to explore publication trends, country contributions, lead author involvement, and the main subjects and topics related to the application of big data in government crisis management. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method was employed, utilizing the Scopus database for the period 2012-2024. The results of this study found a significant increase in the number of publications since 2020, driven by the COVID-19 pandemic and other global crises. China and the United States dominated publication contributions, while the ACM International Conference Proceedings Series was the journal with the most publications. Key findings indicate that the research subjects are multidisciplinary, covering computer science, social sciences, management, and the environment. In addition, cluster analysis identified four main themes in this research: environmental challenges, sustainable development, environmental governance, and future implications. This study also highlights challenges in the implementation of big data by governments, including a lack of cross-sector data integration, privacy issues, and a shortage of experts in data analysis. Although governments in various countries have begun to adopt this technology in their policies, it is necessary to strengthen data protection policies, inter-agency collaboration, and human resource capacity building to optimize the benefits of big data in crisis management. This study provides important insights for governments, academics, and stakeholders to design data-driven strategies to improve resilience to future crises.